Membuat Batik Ecoprint dengan Memanfaatkan Kearifan Lokal untuk Pengembangan Kreatifitas dan Ekonomi Kreatif pada Anak di Desa Marga Bakti - Darman Syafe’i; Henny Rosmawati; Putri Ayu Ogari; Ratika Sari; Salsa Nadillah; Indiana Indiana; Bagas Rahmadani (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Ecoprint is a textile printing technique that uses natural materials, such as leaves, flowers, and plant stems, to create patterns on fabric. This method is environmentally friendly, reduces the use of hazardous chemicals, and produces unique motifs that cannot be repeated. The process involves direct contact between organic materials and fabric, similar to batik techniques but without special tools. Ecoprint is increasingly popular in the world of art and fashion as a sustainable alternative. The target of this PKM is children in Marga Bhakti Village, so that they can learn about the dangers of synthetic dyes and natural dyes and foster environmental literacy. The method applied in this PKM activity is to directly train children in Marga Bhakti Village to carry out eco-print activities directly. This activity can improve the knowledge and skills of children in Marga Bhakti Village. By introducing and also practicing eco-printing through eco-print making training attended by children, it will be able to improve creativity, skills and foster environmental literacy.